Innovations in Islamic Law: Contemporary Applications of Trust and Cash Waqf for Wealth Management in Malaysia - Muhamad Mu'izz Abdullah; Mohammad Abdullah; Akram Mahmad Rabbi; Md Yazid Ahmad; Zubair Amir Nur Rashid Muhamad (MILRev: Metro Islamic Law Review, 2026)
Effective wealth management constitutes a fundamental component of Islamic socioeconomic development, particularly in addressing poverty alleviation and promoting sustainable social welfare. Within the contemporary Islamic financial framework, trust instruments and cash waqf have emerged as strategic mechanisms for mobilising and distributing wealth to support both individual financial security and collective social prosperity. This study aims to evaluate the effectiveness of trust instruments and cash waqf in strengthening the socioeconomic conditions of Muslim communities, reducing poverty, and enhancing welfare outcomes, particularly in the education and healthcare sectors. It further examines the contribution of these instruments from the perspective of maqāṣid al-sharī‘ah and public interest (maṣlaḥah). This research employs a qualitative approach, grounded in a systematic literature review and document analysis of scholarly publications, policy reports, legal documents, and institutional records related to trust and cash waqf practices in Malaysia. A comparative analytical framework is utilised to identify similarities, differences, and complementary functions between the two instruments. The collected data are analysed descriptively to assess their socioeconomic impact and institutional effectiveness. The findings reveal that both trust instruments and cash waqf play a significant role in improving the socioeconomic well-being of Muslim communities through structured asset management, sustainable wealth distribution, and support for public welfare programs. These instruments contribute to educational development, healthcare accessibility, and poverty reduction while promoting long-term financial resilience. Although differing in their legal origins, governance structures, and operational mechanisms, both instruments exhibit comparable strengths in flexibility, tax incentives, and socioeconomic impact. From a maqāṣid al-sharī‘ah perspective, they effectively support the preservation of wealth and the realisation of public welfare. This study contributes to the growing literature on Islamic social finance by offering a comparative understanding of trust and cash waqf as complementary wealth management instruments. The findings provide practical insights for policymakers, financial institutions, and waqf organisations seeking to strengthen Islamic wealth management frameworks in Malaysia and other Muslim-majority contexts.